Eco-physiological aspects of chengal seedlings planted in logged-over forest in Tekai Forest Reserve, Jerantut, Pahang / Farah Shahanim Mohamed Mohidin - Farah Shahanim , Mohamed Mohidin (2018)
The replanting of chengal, an endemic Malaysian hardwood for rehabilitation has gained much prominence lately due to its high economic value. Planting stocks production generally aims to produce quality seedlings that can exhibit good survival and growth after outplanting in a logged-over forest. In this study, the effect of light, age and fertilizer requirements on the growth performance of chengal seedlings raised in the nursery at the Forest Research Institute Malaysia (FRIM) up to planting in a loggedover forest at the Tekai Forest Reserve, Pahang, were determined. Results showed that in the nursery, chengal potted seedlings under 50 % light intensity (LI) treated with NPK Blue fertilizer recorded the highest increment for growth, biomass allocation, plant mineral, soil mineral and physical content as well as physiological parameters compared to 30 and 100 % LI with organic fertilizer applied singly and without any fertilizer application. Meanwhile, in the field it was observed that 1 year 8 month old chengal seedlings given a combination of slow release fertiliser (SRF) and organic fertilizer, showed significantly higher growth, biomass and soil physical content compared to 6- month seedlings treated with either SRF or organic fertilizer after 44 months of planting. On the contrary, 6 months old seedlings exhibited higher soil mineral nutrient and physiological parameters throughout, compared to 1 year 8 month seedlings. Results from this study has provided new insights on the relationship between growth performance in chengal and biomass allocation, soil physical and mineral characteristics and its physiological processes, from nursery stage up to after outplanting in a loggedover forest.